Deficient fear recognition in regular cocaine users is not attributable to elevated impulsivity or conduct disorder prior to cocaine use. (June 2013) - Morgan, MJ; Marshall, JP
We previously reported that regular recreational intranasal cocaine users exhibit impaired recognition of facial expressions of fear compared to occasional cocaine users and cocaine-naïve controls. The aim of the present study was to re-investigate this phenomenon after controlling for impulsivity, conduct disorder (CD) and anti-social personality disorder (ASPD). We employed a cross-sectional design to compare 31 cocaine-naïve participants, 35 occasional cocaine users and 20 regular recreational cocaine users. An emotional facial expression (EFE) task which comprised a male and a female face expressing six basic emotions morphed to differing degrees of emotional intensity was administered together with questionnaires to assess: CD, ASPD and impulsiveness. ASPD was not a significant covariate for EFE performance but impulsiveness and CD were significant covariates. After treating impulsiveness and CD as covariates we again observed a group difference in fear recognition ability attributable to the particularly impaired performance of regular cocaine users. This suggests that, although elevated impulsiveness and CD before the age of 15 years, may predispose a relative inability to recognize facial expressions of fear in adulthood, subsequent regular recreational use of cocaine represents an additional factor that is specifically associated with a selective deficit in fear recognition.